2010
DOI: 10.3989/scimar.2011.75n1009
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of <i>Neorossia caroli</i> (Cephalopoda: Sepiolidae) in the Aegean Sea

Abstract: SUMMARY: A total of 171 specimens of Neorossia caroli were collected by monthly sampling using a bottom trawl with 44-mm mesh size. The depth range of trawls varied between 150 and 550 m. The maximum size (dorsal mantle length, ML) was 41 mm for males and 50 mm for females. Seasonal gonadal stages of both sexes were examined using a gonadosomatic index. It has been observed that the pattern of ovulation of N. caroli is asynchronous and that spawning is continuous. The potential fecundity of females ranged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The reason for this phenomenon is the unidirectional impact of 3 main environmental factors that are different between the eastern and western Mediterranean: productivity, temperature, and salinity (Sonin et al, 2007). This study, combined with previous results (Salman, 1998;Önsoy and Salman, 2005;Salman and Önsoy, 2010;Salman, 2011), testifies that Mediterranean nanism can also be seen in cephalopods.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The reason for this phenomenon is the unidirectional impact of 3 main environmental factors that are different between the eastern and western Mediterranean: productivity, temperature, and salinity (Sonin et al, 2007). This study, combined with previous results (Salman, 1998;Önsoy and Salman, 2005;Salman and Önsoy, 2010;Salman, 2011), testifies that Mediterranean nanism can also be seen in cephalopods.…”
Section: Discussionsupporting
confidence: 59%
“…Boyle et al (1988) reported that cephalopods' first maturation length decreases from the Atlantic to the Mediterranean, and other results on other Mediterranean cephalopods such as Sepietta oweniana (Salman, 1998), S. officinalis (Önsoy and Salman, 2005), Rossia macrosoma (Salman and Önsoy, 2010), and Neorossia caroli (Salman, 2011) also demonstrated a decrease in the minimum size of mature animals from west to east that is in agreement with our results on S. orbignyana.…”
Section: Discussionmentioning
confidence: 99%
“…As R. macrosoma is an intermittent spawner (Salman and Önsoy 2010), like other sepiolin species (e.g. Gabel-Deickert 1995;Bello and Deickert 2003;Salman and Önsoy 2010;Salman 2011), it is possible that females return to a previous egg batch to continue spawning. However, it was not possible to determine if, in our observations, already existing egg batches were laid by the same female or derived from a conspecific.…”
Section: Resultsmentioning
confidence: 99%
“…Different numbers of spermatangia can be observed in subfamily Rossinae species, such as Rossia molleri 6-21 (Hoving et al, 2009);Semirossia.patagonica 2-19 (Önsoy et al, 2008); Neorossia caroli 1-30 (Salman, 2011), which do not contain bursa copulatrix. .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in general, sepiolids spawn throughout the year whether their lifetime is shorter than a year like the Sepietta oweniana or more than a year such as Neorossia caroli (Boletzky 1975;Salman, 1998Salman, , 2011Önsoy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%